1986
DOI: 10.2527/jas1986.624968x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Development and Body Composition in Three Genetic Stocks of Swine

Abstract: Differences in growth, chemical body composition and visceral organ development were evaluated in three genetic stocks: Beltsville Highfat (HF) and Lowfat (LF) Duroc-Yorkshire composites and a Hampshire X Large White cross (CX). Ten sets of littermate barrows were used from each stock. One pig from each set was slaughtered at 10, 17 and 24 wk of age. After slaughter, each pig was dissected into three fractions: carcass, head and feet, viscera and blood. Backfat was measured at three locations and visceral orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 12 publications
6
25
0
1
Order By: Relevance
“…The late maturing nature of fat, observed by many authors (Davies and Kallweit, 1979;Shields et al, 1983;Tess et al, 1986;Fortin et al, 1983;Gu et al, 1992) was also confirmed here. Wagner et al (1999) observed that the exponential equation they used described the lipid deposition as sigmoid, whereas the allometric and quadratic functions were more linear in nature.…”
Section: Temporal Growth -Fatsupporting
confidence: 89%
“…The late maturing nature of fat, observed by many authors (Davies and Kallweit, 1979;Shields et al, 1983;Tess et al, 1986;Fortin et al, 1983;Gu et al, 1992) was also confirmed here. Wagner et al (1999) observed that the exponential equation they used described the lipid deposition as sigmoid, whereas the allometric and quadratic functions were more linear in nature.…”
Section: Temporal Growth -Fatsupporting
confidence: 89%
“…Robelin and Geay (1978) estimated allometric growth coefficients for protein and water of 1.06 and 0.98, respectively, in a number of literature sources describing studies that had included various breeds. Tess et al (1986) estimate for barrows ranged from 1.10 to 1.13 for protein and ranged from 0.95 to 0.97 for water in relation to FFW. These allometric growth coefficients for cattle and pigs show a similar trend in terms of changes in protein and water deposition in the fat-free empty body.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of liver and spleen the AGRs decreased with increasing carcass weight (P < 0.001 ). Heavier non-carcass components have also been reported for pigs from lines selected for low backfat depths (Tess et al 1986).…”
Section: Femur Shapementioning
confidence: 93%